The effect of strategic alignment on the reputation of the organization - abdulkreem, Sarah ahmed; saeed, Hadeel kadhm (Journal of Economics and Administrative Sciences, 2021)
The current study aims to determine the extent of SOMO’s interest in strategic alignment operations and whether this interest is sufficient to be reflected in enhancing its organizational reputation. The field of research was in the oil marketing company SOMO. The managers in the top management within this company were targeted and the questionnaire was used as a data collection tool. The study population (109), (105) questionnaires were distributed, (94) questionnaires and (11) questionnaires were not retrieved, and the valid questionnaires had reached (91) and the analytical and descriptive approach was used for the study, the current research found to find A direct relationship and a positive effect of strategic alignment on the reputation of the organization, and the sub-variable had the highest impact on the reputation of the organization is (Governance), whichever this research proves the existence of the proposed relationship and effect between strategic alignment and the reputation of the organization, and through the researcher access to previous local and global studies did not find A study looks at the relationship between these two variables